Cuticular waxes of the holm (Quercus ilex l. subsp. ballota (desf.) samp.) and cork (Q. suber l.) oaks - Martins, C M C; Mesquita, S M M; Vaz, W L C (Phytochemical Analysis, 1999)
The epicuticular leaf waxes of young leaves of the Holm oak (Quercus ilex L. ssp. ballota (Desf.) Samp.) and the cork oak (Q suber L.) were extracted in chloroform and separated into their constituent wax classes by preparative thin layer and high pressure liquid chromatography. The wax coverage was about 125 μg/cm2 in Q. suber and about 71 μg/cm2 in Q. ilex. The main classes encountered (by weight) were odd chain n-alkanes (9% in Q. ilex, and 4–27% in Q. suber) and even chain amphiphilic compounds. The major classes of amphiphilic compounds were n-alkan-1-ols (20–27% in Q. ilex, and 18–50% in Q. suber), n-alkanals (<3% in Q. ilex, and up to 25% in Q. suber), n-alkanoic acids (11–12% in Q. ilex, and <5% in Q. suber) and n-alkyl esters (50–56% in Q. ilex, and 25–45% in Q. suber). The major components of each class, identified by gas chromatography coupled to mass spectrometry were C29 for the n-alkanes (54–58% in Q. ilex, and 47–57% in Q. suber), C24 for the n-alkan-1-ols (78–87% in Q. ilex, and 77–93% in Q. suber), C30 for the n-alkanals (up to 57% in Q. ilex, and up to 77% in Q. suber), C22 and C24 for the n-alkanoic acids in Q. ilex (39–62%) and C30 in Q. suber (49%). The n-alkyl esters were composed mainly from C22 and C24n-alkanoic acids (∼38%) and n-alkan-1-ols (43–54%) in Q. ilex, whereas in Q. suber these esters were composed mainly from C22 and C24n-alkanoic acids (44–52%) and C20 and C22n-alkan-1-ols (32–66%). In addition to the above compounds, trace amounts (<5%) of C28 and C30n-alkenes and the triterpenone, friedelin, were encountered in Q. suber and both plant waxes contained small amounts of the triterpenols α- and β-amyrin (5–9% of the total alkanol content). The variability observed in the chemical composition of the leaf waxes were attributable to seasonal causes and/or leaf age. Copyright © 1999 John Wiley & Sons, Ltd.
Keywords: chemical composition; cuticle; cuticular waxes; Quercus ilex; Quercus suber

Cuticular waxes of the holm (Quercus ilex l. subsp. ballota (desf.) samp.) and cork (Q. suber l.) oaks - Martins, C. M. C.; Mesquita, S. M. M.; Vaz, W. L. C. (Phytochemical Analysis, 1999)
The epicuticular leaf waxes of young leaves of the Holm oak (Quercus ilex L. ssp. ballota (Desf.) Samp.) and the cork oak (Q suber L.) were extracted in chloroform and separated into their constituent wax classes by preparative thin layer and high pressure liquid chromatography. The wax coverage was about 125 μg/cm2 in Q. suber and about 71 μg/cm2 in Q. ilex. The main classes encountered (by weight) were odd chain n-alkanes (9% in Q. ilex, and 4–27% in Q. suber) and even chain amphiphilic compounds. The major classes of amphiphilic compounds were n-alkan-1-ols (20–27% in Q. ilex, and 18–50% in Q. suber), n-alkanals (<3% in Q. ilex, and up to 25% in Q. suber), n-alkanoic acids (11–12% in Q. ilex, and <5% in Q. suber) and n-alkyl esters (50–56% in Q. ilex, and 25–45% in Q. suber). The major components of each class, identified by gas chromatography coupled to mass spectrometry were C29 for the n-alkanes (54–58% in Q. ilex, and 47–57% in Q. suber), C24 for the n-alkan-1-ols (78–87% in Q. ilex, and 77–93% in Q. suber), C30 for the n-alkanals (up to 57% in Q. ilex, and up to 77% in Q. suber), C22 and C24 for the n-alkanoic acids in Q. ilex (39–62%) and C30 in Q. suber (49%). The n-alkyl esters were composed mainly from C22 and C24n-alkanoic acids (∼38%) and n-alkan-1-ols (43–54%) in Q. ilex, whereas in Q. suber these esters were composed mainly from C22 and C24n-alkanoic acids (44–52%) and C20 and C22n-alkan-1-ols (32–66%). In addition to the above compounds, trace amounts (<5%) of C28 and C30n-alkenes and the triterpenone, friedelin, were encountered in Q. suber and both plant waxes contained small amounts of the triterpenols α- and β-amyrin (5–9% of the total alkanol content). The variability observed in the chemical composition of the leaf waxes were attributable to seasonal causes and/or leaf age. Copyright © 1999 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd.
Keywords: chemical composition; cuticle; cuticular waxes; Quercus ilex; Quercus suber